Volumetric Modulated Arc Therapy Craniospinal Irradiation Utilizing a Vertebral Body Sparing Approach: An Alternative Approach to Improve Access and Minimize Toxicity - Haley K. Perlow, MD; Jennifer K. Matsui, PhD; Ashlee Ewing, CMD; Catherine Cadieux, CMD; Khaled Dibs, MBBS; Rituraj Upadhyay, MD; Dukagjin M. Blakaj, MD, PhD; Sasha J. Beyer, MD, PhD; Evan M. Thomas, MD, PhD; John C. Grecula, MD; Raju R. Raval, MD, DPhil; Joshua D. Palmer, MD (Advances in Radiation Oncology, 2024)
Introduction: Craniospinal irradiation (CSI) is indicated for adult patients diagnosed with leptomeningeal disease (LMD). Proton-based vertebral body sparing (VBS) CSI has been explored with pediatric patients to minimize hematologic toxicity; however, utilization of VBS in an adult population is limited. A recent phase II trial has shown efficacy of proton-based CSI to treat non-small cell lung and breast cancer with LMD. We hypothesize that VBS CSI using volumetric modulated arc therapy (VMAT) could also effectively reduce dose to vertebral bodies and surrounding organs at risk, minimizing toxicity for adult patients with LMD and comparing favorably to proton-based CSI. Methods and Materials: Consecutive patients with LMD received VMAT VBS CSI, 30 Gy in 10 fractions, as a part of a prospective registry. Full VMAT arcs for the brain fields matched to 2 spine isocenters for the upper and lower spine were created using limited posterior arcs. To further decrease the vertebral body dose, an avoid entry and exit contour was created. Acute toxicity data were collected using Common Terminology Criteria for Adverse Events v5. Results: Ten adult patients were treated in this cohort. One patient experienced grade 2 neutropenia with the remaining 9 experiencing grade 1 hematologic toxicity. Three patients experienced grade 2 gastrointestinal toxicity with the remaining 7 experiencing grade 1 nausea. No patient experienced grade 3+ toxicities in this cohort. One patient experienced a 5-day delay in systemic therapy initiation due to neutropenia; otherwise, all patients planned for systemic therapy started without delay. Conclusions: In this study, VMAT VBS CSI led to acceptable toxicity compared with patients treated with proton CSI on a phase 2 clinical trial. Given its promising early results, future prospective evaluation of the technique is warranted.